Effect of claw horn lesion type and severity at the time of treatment on outcome of lameness in dairy cows - Miguel-Pacheco, Giuliana G.; Thomas, Heather J.; Huxley, Jonathan N.; Newsome, Reuben F.; Kaler, Jasmeet (Elsevier, 2017)
Prompt diagnosis and treatment of claw horn lesions in cattle affects the likelihood of recovery; however, it is unknown if the type of lesion influences the likelihood of recovery. The aim of this study was to investigate whether the type, severity and frequency of claw horn lesions in newly lame cows (lame for no more than 2 weeks) at the time of corrective foot trimming affects the probability of recovery from lameness after treatment. The images of 112 feet (224 claws) from newly lame cows (n = 112; lame in only one hind foot), which were treated with a standardised therapeutic hoof trim only, were used to score claw horn lesions (sole ulcer, sole haemorrhage, white line haemorrhage or white line separation). Most cows (n = 107/112; 95.5%) were classified as mildly lame at the time of treatment. The proportion of cows that recovered 2 weeks after therapeutic hoof trimming was 88/112 (78.6%). Results of a multilevel logistic regression model indicated that severely lame cows were less likely to recover than those that were mildly lame (odds ratio, OR, 0.16; P = 0.04). White line haemorrhage had a significant negative impact on the likelihood of recovery from lameness (OR 0.14; P > 0.01); however, recovery of cows with white line haemorrhage was positively associated with the length of the lesion (OR 1.05; P = 0.03). This latter finding may be associated with the severity of the lesion, since mild claw horn lesions affected a significantly larger area of the claw than more severe lesions. The length and type of claw horn lesion were associated with recovery from lameness.